MAIDAKUTIBVISA - Developing networks of permanence and impermanence within Mbare, Harare, Zimbabwe, through the preservation and adaptation of informal infrastructure. - Mashiri, Tadiwa (School of Architecture, Planning and Geomatics, 2023)
Why? This thesis investigation addresses the issue of dilapidated infrastructure within the informal trading network of Mbare, Harare, Zimbabwe and the informal markets that exist there. This issue of dilapidated and inad - equate infrastructure comes as a hindrance to the struc - tures and spaces that vendors occupy and rely on to make a living within this context and because of this issue, this context has faced problems such as congestion, constant threat of losing trading structures to fire and harassment from government and police forces because of the state of the trading spaces. How? To address this issue this thesis investigation looks at precedents of existing market spaces within the global south such as the Warwick Junction in Durban, South Africa, (amongst many) to understand and create functional market spaces with adaptable, affordable, and sustainable infrastructure within the context of Mbare. The creation of robust physical prototypes, such as stalls, furniture, façade elements and outdoor recreational spaces, using the avail - able materials and knowledge within this area is another step that is taken to address spatial and infrastructural issues in the areas of Mupedzanhamo, Magaba and Mbare Musika markets within this context. This thesis investigation also looks at the application and investigation of spatial theories such as the Metabolist theory and critical regionalism to solve the spatial issues that currently exist within this nomadic and ever-changing context. What? To test these the results of my dissertation investigation, the design and creation of market spaces that deal with the issues of congestion and dilapidated infrastructure within this area will take place. These market spaces will not act as replacements for the existing Mupedzanhamo, Magaba and Mbare Musika but will instead act as an extension of their existing spatial networks thus providing vendors with more space to trade and doing so, making a living. programs that did not previously exist allowing the creation of employment and training for the informal traders and vendors. Conclusion. The aim of this investigation is to assess whether the existing knowledge within the informal context of Mbare can be used to address some of the infrastructural issues that currently exist. This investigation also aims to see whether the role of the Architect as a collaborator within the design of the informal market context can allow traders to improve the means in which they make a better living.